Consumers’ perception in purchasing cooking palm oil in Bukit Ibam, Muadzam shah, Pahang / Muhamad Faiez Rasuddin - Rasuddin, Muhamad Faiez (Faculty of Plantation and Agrotechnology, 2017)
The study of this research is about the perception of the consumer towards purchasing cooking palm oil in Bukit Ibam., Pahang. Three main objectives of this study are to determine the level of awareness, acceptance level and demand of cooking palm oil among the consumer. Methodology used was questionnaire which applied the random sampling method by using Crosstab, Chi-Square analysis and factor analysis. The result showed based on Factor Analysis Test, the level of awareness is 0.705, level of acceptance is 0.527 and demand factor is 0.532. The main factor towards consumers on purchasing cooking palm oil which is based on Factor Analysis Test is level of awareness. From the level of awareness, it separate into the three main factor which is health factor, knowledge factor and energy factor. As a result, people should more concern about the advantages and disadvantages of cooking palm oil. Other research also should be done to others place to identify is there the same factor or will get another factor about the perception towards cooking palm oil.